THANK YOU VOLUNTEERS, THANK YOU USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, 11 January 2015 – The Minister of Education II, Dato' Seri Idris Jusoh expressed his thanks and appreciation to all involved in the postflood relief operations in Kelantan. "I wish to extend my sincere appreciation to the 17,000 volunteers from the local universities involved and various institutions including the community colleges, who have worked very hard over the past 10 days to help clean up about 160 schools or 96% of the total schools affected by the floods," said Idris.